China’s fight against terrorism at sea - Talijan Miroslav M.; Mitić Vlada M.; Šuai Zeng (Војно дело, 2016)
As the largest share of China’s exports and imports goes across the South China Sea and the Strait of Malacca, the Chinese national interest is exactly to put their anti-terrorism policies on a legal footing through anti-terrorism regulations, to equip and properly organize its forces for the fight against terrorism, as well as to participate in related international exercises and operations. In achieving this goal, China is faced with numerous obstacles, such as: the lack of respective legal regulations and a large number of anti-terrorist forces, which are inadequately coordinated and poorly equipped and trained. Also, territorial disputes over maritime areas with the countries bordering the South China Sea, and frequent meddling of the great powers, like the United States and Japan, prevent China to build bilateral relations with these countries for the joint fight against terrorism. On the other hand, China’s active participation in international exercises and operations relating to the fight against pirating and terrorism at sea increase China’s capabilities to protect its own national interests.